The readiness of the spontaneous reporting system for COVID-19 vaccines safety monitoring in Croatia - Kovačić Barbara; Pavičić Morana; Skvrce Nikica Mirošević; Tomić Siniša (Acta Pharmaceutica)
We aimed to identify whether a spontaneous reporting system (SRS) in Croatia could timely identify and confirm signals for COVID-19 vaccines. Post-marketing spontaneous reports of adverse drug reactions (ADRs) following COVID-19 immunisation reported to the Agency for Medicinal Products and Medical Devices of Croatia (HALMED) were extracted and analysed. 6624 cases reporting 30 655 ADRs following COVID-19 immunisation were received from 27th December 2020 to 31st December 2021. Available data in those cases were compared with data available to the EU network at the time when signals were confirmed and minimisation measures were implemented. 5032 cases, reporting 22 524 ADRs, were assessed as non-serious, and 1,592 cases, reporting 8,131 ADRs as serious. The most reported serious ADRs, which were listed in the MedDRA Important medical events terms list, were syncope (n = 58), arrhythmia (n = 48), pulmonary embolism (n = 45), loss of consciousness (n = 43), and deep vein thrombosis (n = 36). The highest reporting rate had Vaxzevria (0.003), followed by Spikevax and Jcovden (0.002), and Comirnaty (0.001). Potential signals were identified, however, they couldn’t be timely confirmed solely on cases retrieved by SRS. In order to overcome the limitations of SRS, active surveillance and post-authorisation safety studies of vaccines should be implemented in Croatia.